Empowering Maritime Generation Z Students to Develop a Digital Entrepreneurial Mindset through Self-Efficacy & Cognitive Flexibility - Riki Wanda Putra; Bambang Hermanto; Elfira Wirza; Nazarwin; Hasri Devin (Bulletin of Pedagogical Research, 2025)
This study examines an empowerment program designed to develop a digital entrepreneurial mindset among Generation Z maritime students by strengthening self-efficacy and cognitive flexibility. Responding to the accelerating digitalization of the maritime sector, the program aimed to shift student perspectives from traditional seafaring roles toward innovation-driven, technology-based entrepreneurship. Adopting a Participatory Action Research (PAR) model, the intervention involved 118 second-semester students at Politeknik Pelayaran Sumatera Barat and comprised stages of preliminary assessment, socialization and motivational seminars, two-day training workshops using Creative Problem Solving and Design Thinking, digital business idea simulations, mentoring, and reflective evaluation. Data collection included pre–post surveys, direct observation, written student reflections, facilitator notes, and triangulation across sources; qualitative descriptive analysis identified thematic changes in self-efficacy, cognitive flexibility, and entrepreneurial orientation. Post-intervention findings show notable increases in students’ confidence to express ideas, make decisions, and assume leadership roles, alongside enhanced cognitive flexibility manifested in multi-perspective problem solving and creative solution generation. Participants produced viable digital maritime business concepts (e.g., vessel-tracking applications, online seafarer training platforms, and logistics services), and demonstrated improved communication, teamwork, and pitching skills. The study recommends curriculum integration, establishment of a campus digital maritime incubator, stakeholder engagement for industry linkage, and longitudinal evaluation to sustain and scale outcomes. Overall, the intervention advances a replicable model for preparing adaptive, innovative maritime graduates capable of contributing to Indonesia’s digital maritime economy.